1990
DOI: 10.1177/002221949002301006
|View full text |Cite
|
Sign up to set email alerts
|

Reading Disabilities and the Effects of Colored Filters

Abstract: The efficacy of a controversial treatment, using colored filters to remediate reading disabilities, was measured empirically, with colored overlays placed over reading material on white paper. Irlen's (1983) method is to prescribe specific tinted filters as lenses that she claims filter specific light frequencies and remove a range of perceptual disorders that adversely affect reading and related learning performance. Irlen calls this condition "scotopic sensitivity" and claims it is a significant factor in a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0
1

Year Published

1993
1993
2022
2022

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(24 citation statements)
references
References 7 publications
0
23
0
1
Order By: Relevance
“…209,211,213 This group with Irlen symptoms showed a high percentage of convergence and accommodative dysfunction, which challenges the claim that the symptoms of SSS are not attributable to vision abnormalities. 211,213 This finding highlighted the need for a formal definition of SSS. The main flaws in this study were that multiple treatments were given to the Irlen-treatment group and the unacceptably large loss of subjects.…”
Section: Colored Lenses and Overlaysmentioning
confidence: 82%
See 3 more Smart Citations
“…209,211,213 This group with Irlen symptoms showed a high percentage of convergence and accommodative dysfunction, which challenges the claim that the symptoms of SSS are not attributable to vision abnormalities. 211,213 This finding highlighted the need for a formal definition of SSS. The main flaws in this study were that multiple treatments were given to the Irlen-treatment group and the unacceptably large loss of subjects.…”
Section: Colored Lenses and Overlaysmentioning
confidence: 82%
“…Overall, study results have been inconsistent 208,216,223,232 ; many studies have shown that colored overlays and filters are ineffective, 205,214,217,[233][234][235] but a few studies have reported partial positive results. 212,213,218,222,224,231 Many unreported studies have shown no effect of colored filters on measures of either reading performance or SSS symptoms. Also, many of the studies cited as proof of Irlen-lens efficiency actually have been found to be inconclusive after deeper analysis.…”
Section: Colored Lenses and Overlaysmentioning
confidence: 99%
See 2 more Smart Citations
“…Ritchie et al (2011) also found that there was no immediate benefit of colored overlays on reading difficulties. On the contrary, (O'Connor et al 1990) found improved reading rate and accuracy when the individual with reading difficulties read with the preferred color of overlay. found a significant difference in the rate of reading in the group using a colored overlay compared to a control group.…”
Section: Introductionmentioning
confidence: 83%